TINJAUAN KRIMINOLOGIS TERHADAP KEJAHATAN PEMBUNUHAN BERENCANA YANG DILAKUKAN OLEH KEKASIH KORBAN (STUDI KASUS PUTUSAN NOMOR: 843/Pid.B/2019/PN PTK) - NIM. A1011201255, YUNITA SAFITRI (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract Criminology as a tool to help find the causes of crime so that it directs its study to processes by looking for factors that cause crimes against life, namely the crime of premeditated murder. The crime of premeditated murder that occurred in the city of Pontianak was a case of premeditated murder committed by the victim's lover in 2019. This research aims to reveal the factors causing the crime of premeditated murder committed by the victim's lover. This research uses sociological juridical research with data collection techniques through interviews with respondents who are directly related to this research. Based on the results of the research and discussion, the researcher drew the conclusion that the factors that caused the perpetrator to take the victim's life were internal and external factors. Keywords: Criminology, Premeditated murder, Victim